The crystal structure of 6,6′-(((2-(dimethylamino)ethyl)azanediyl)bis(methylene))bis(2-chloro-4-methyl phenolate-κ4N,N′,O,O′)-(pyridine-2,6-dicarboxylato-N,O,O′)-titanium(IV), C27H27Cl2N3O6Ti - Yang Mingjun; Wang Canghai (Zeitschrift für Kristallographie - New Crystal Structures)
C27H27Cl2N3O6Ti, monoclinic, P21/c (no. 14), a = 11.609(4) Å, b = 21.476(7) Å, c = 13.504(4) Å, β = 109.881(9)°, V = 3166.2(18) Å3, Z = 4, Rgt(F) = 0.0623, wRref(F2) = 0.1945, T = 100(1) K.